ChemInform Abstract: Synthesis of Trifluoromethylated Acetylenes via Copper‐Catalyzed Trifluoromethylation of Alkynyltrifluoroborates. Issue 13 (18th March 2013) - Zheng, Huidong; Huang, Yuanyuan; Wang, Zhiwei; Li, Huaifeng; Huang, Kuo‐Wei; Yuan, Yaofeng; Weng, Zhiqiang
Abstract The preparation of the title compounds is achieved via electrophilic trifluoromethylation of aromatic alkynes and the aliphatic analogue (IV) with Togni′s reagent (I).